THE ANALYSIS OF THINKING AND CREATIVITY SKILLS OF JUNIOR HIGH SCHOOL STUDENTS USING SCIENCE, TECHNOLOGY, AND SOCIETY APPROACH IN SCIENCE LEARNING - Fianti, Fianti; Rulyaimah, Rulyaimah; Susanto, Hadi (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
The ability to think creatively in improving the quality of education is considered as a very vital source for a nation. If carefully observed, education development efforts have not been optimal, it is because the teacher does not know the extent to which student’s creative thinking ability. Therefore, in certain subjects (IPA) that require high creative thinking skills, there are still many students who lack value. The aims of the study are to determine the ability of creative thinking and the influence of learning models of Community Technology Science (CTS) in improving the creativity of junior high school students on global warming materials. The research design used is descriptive quantitative. The population in this study are students of class VII SMP N 1 Jakenan. The sample is determined by purposive sampling. Test methods, observations, and questionnaires were used to collect research data. The results showed that students creative thinking ability using CTS model for high category was 12%, medium 65%, and low 23% based on test, while for creative attitude, 100% of students were in medium category. CTS models influence on the ability of creative thinking of students increased by 6%.